Genomics of disease - Gustafson, J.P. (Stadler genetics symposia series,, 2008)
Genomics of Disease Edited by: Jerry Taylor, University of Missouri, Columbia, Missouri Gary Stacey, University of Missouri, Columbia, Missouri J. Perry Gustafson, USDA-ARS, University of Missouri, Columbia, Missouri Genomics of Disease is the 24th volume in the Stadler Genetics Symposium series published by Springer, which has, over many years, served as a comprehensive collection of current trends and hot topics in the field of genetics. The current volume summarizes recent progress in our attempts to characterize the genomics of plant and animal diseases. Authoritative analytical reviews are specialized to be attractive to professional researchers, teachers, and students, while also being appealing to a wider audience of scientists in related disciplines. Genomics of Disease offers essential reference material for any scientist or teacher working in the fields of plant and animal diseases. Coverage of key areas of both animal and plant disease is a unique feature of this volume and one that allows direct comparisons between the systems. All academics, scientists, and industry professionals that desire to take advantage of the most up-to-date information on the continuously emerging and expanding field of the genomics of plant and animal diseases will find it an invaluable resource. Key features: * Comprehensive coverage of current topics dealing with the genomics of plant and animal diseases * Chapters authored by the key scientists in the field * Accessible utility in a single volume reference About the Editors: Jerry Taylor is a Professor of Animal Sciences and of Genetics and holds the Wurdack Chair in Animal Genomics in the Division of Animal Sciences at the University of Missouri-Columbia. He has received in excess of $11 million in competitive research funding as PI or co-PI, has mentored 9 postdoctoral fellows and has chaired or co-chaired 34 M.S. and Ph.D. graduate programs. Along with his co-investigators and graduate students he has authoredr-reviewed research articles, 4 book chapters and 5 patents. He has served on the Scientific Advisory Board for Sigma-Aldrich Biotechnology in St Louis, MO and was cofounder, board member and a senior executive of GenomicFX an agricultural biotechnology company. He has been the recipient of the Texas A&M University Vice-Chancellor’s Awards for Teaching and Team Research. He is a Fellow of the American Association for the Advancement of Science. Gary Stacey is an Endowed Professor of Plant Sciences and Associate Director of the National Center for Soybean Biotechnology at the University of Missouri-Columbia. He also holds joint appointments in the Division of Biochemistry and Department of Molecular Microbiology and Immunology. He has authored or co-authored 135 peer-reviewed research articles, 72 book chapters, 14 books, including this volume, and 9 patents. He is past senior editor of the journals Molecular Plant-Microbe Interactions and Plant Physiology. He serves on various advisory boards and currently serves on the editorial boards of the journals Bioenergy Research, BMC Plant Genomics and Systems Biology, and Journal of Integrative Plant Biology. In 2005, he was elected by the soybean community to a three-year term on the National Soybean Genetics Executive Committee. Perry Gustafson is a Research Geneticist with the USDA-ARS, and an Adjunct Professor at the University of Missouri, Columbia. He is a Fellow of the American Society of Agronomy, the Crop Science Society of America, and the American Association for the Advancement of Science. He has received numerous honors and awards, and is an associate editor on several international journals. Roles of Plant Hormones in Plant Resistance and Susceptibility to Pathogens -- Canine Genetics Facilitates Understanding of Human Biology -- Xanthomonas oryzae pv. oryzae AvrXA21 Activity Is Dependent on a Type One Secretion System, Is Regulated by a Two-Component Regulatory System that Responds to Cell Population Density, and Is Conserved in Other Xanthomonas spp. -- Unraveling the Genetic Mysteries of the Cat: New Discoveries in Feline-Inherited Diseases and Traits -- Variation in Chicken Gene Structure and Expression Associated with Food-Safety Pathogen Resistance: Integrated Approaches to Salmonella Resistance -- Functional Genomics and Bioinformatics of the Phytophthora sojae Soybean Interaction -- Canine SINEs and Their Effects on Phenotypes of the Domestic Dog -- Ovine Disease Resistance: Integrating Comparative and Functional Genomics Approaches in a Genome Information-Poor Species -- Integrating Genomics to Understand the Marek’s Disease Virus – Chicken Host–Pathogen Interaction -- Combining Genomic Tools to Dissect Multifactorial Virulence in Pseudomonas aeruginosa -- Genetic Dissection of the Interaction Between the Plant Pathogen Xanthomonas campestris pv. vesicatoria and Its Host Plants -- Structure and Function of RXLR Effectors of Plant Pathogenic Oomycetes -- The Biotrophic Phase of Ustilago maydis: Novel Determinants for Compatibility -- Virulence Evolution in Malaria -- The Ins and Outs of Host Recognition of Magnaporthe oryzae.